Swedish - Finnish glossary: waste words - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary containing waste words. Published in Kieliviesti 3/2005. Contains approximately 210 entries. 2005.

Svensk-sverigefinsk ordlista med avfallsord. Publicerad i Kieliviesti 3/2005. Innehåller ca 210 ord. 2005.
Svensk-finsk ordlista: avfallsord
Keywords: recycling; återvinning; waste disposal and handling; avfallshantering; wastes; avfall; refuse; sopor; glossary; ordlista; vocabulary; ordlista; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur